RESULTS OF SURGICAL TREATMENT OF LIVER ECHINOCOCCOSIS IN CHILDREN (Herald of the National Children's Medical Center, 2024)
Echinococcosis is one of the urgent problems of pediatric surgery. The disease can affect all organs, only one develops most often in the liver (50-77%). The recurrence of echinococcosis remains at the upper level and ranges from 1.1% to 31.8%.